Proses Transaksi Sewa Ruangan Berbasis Virtual Office - Endang Supriyadi; Maya Sofiana; Novitri Landong Namora Sihombing; Adelia Oktaviany Putri; Anisa Kemala Dewi; Chintya Dewi Harum (CV ODIS, 2022)
Virtual Office is an alternative option for business people, not only startups or small-scale businesses but also large and medium-sized companies that are already running. This is an opportunity for office rental entrepreneurs to optimize their Virtual Office business. The government has previously given more attention to the existence of Virtual Offices by making regulations that provide convenience for virtual office companies. The purpose of this study was to determine the process of office rental transactions based on virtual office (Case Study: PT Pilar Loka Karya). Data collection techniques, data obtained from direct observations, interviews with informants, and literature. The research method used is descriptive with a case study approach. The results can be concluded that PT Pilar Loka Karya has optimally processed office rental transactions based on virtual office.